Pelatihan Penyusunan dan Pengolahan Menu DASHAT (Dapur Sehat Atasi Stunting) di Desa Solodiran Kabupaten Klaten - Dyah Intan Puspitasari; Sadna Izzatul Azka; Ayu Sherlinda Putri (Abdi Geomedisains, 2025)
Stunting is one of the health problems that has become a priority to address in Indonesia. Solodiran Village is one of the stunting-focus (locus) villages in Klaten Regency. Stunting prevention interventions need to be carried out as early as possible, even before the baby is born, starting from when women are still in their teenage years. Programs to support the reduction of stunting cases can be carried out by providing education to at-risk groups, such as women of childbearing age, pregnant women, breastfeeding mothers, and mothers of toddlers. The Dapur Sehat Atasi Stunting (DASHAT) program, launched by the National Population and Family Planning Board (BKKBN), is a program aimed at being a center for nutrition and services for children with stunting. This program includes a healthy menu that uses local products, which also helps empower and improve the welfare of the surrounding community. Solodiran Village has various local food sources such as various vegetables, chicken, and catfish, which can be utilized as healthy food sources to prevent stunting. The program offered for stunting prevention in Solodiran Village, by adopting the DASHAT program, which includes activities such as education using PowerPoint media about how to create DASHAT menus, followed by demonstrations on processing and serving DASHAT menus. This activity was carried out successfully with 20 participants. The results of the activity showed an increase in the participants' knowledge after attending the education, as indicated by an average post-test score of 8.7 (categorized good knowledge). Participants' understanding of processing balanced nutrition menus based on local food also improved after the demonstration on how to process and serve DASHAT menus. Through this program, it is hoped that the knowledge and skills of the target group in preparing healthy, balanced meals will improve, which could help reduce stunting cases, especially in Klaten Regency.